PENYEBARAN HAMA KEPINDING TANAH DAN MUSUH ALAMINYA PADA PERTANAMAN PADI SAWAH DI SULAWESI UTARA - Paendong, Evi; Pelealu, Jantje; Rimbing, Jimmy (Universitas Sam Ratulangi, 2011)
ABSTRACT Bedbug is the major pest in paddy fields in North Sulawesi. The pest attacks on vegetative and generative phase of rice . The species of pest attacking on paddy fields in North Sulawesi is unknown. The study aimed to evaluate the spread of bedbug ground pests, to identify the pest species as well as natural enemies of the pest at the ecosystem of paddy fields in North Sulawesi. The result showed that the pest had spread to paddy field in Bolaang Mongondow, South Minahasa and Southeast Minahasa. In Minahasa regency, the pest had not been detected. In terms of population density of pest bugs , the highest was found in Bolaang Mongondow which was 14.67 individual per 20 times of swinging followed by South Minahasa which was 10.33 individual. The lowest was found in Southeastern Minahasa which was 0.67 individuals. There were eight types of natural enemies of the pest in soil ecosystem of paddy fields in North Sulawesi. The eight types of natural enemies of the pest were seven predator and one parasitoid. The one parasitoid was Telenomus sp. The seven predator were Micraspis crocea, Methioche sp, Anaxipha sp, Oxyopes javanus, Tetragnatha sp, Lycosa sp and Chilomenes sp. Keywords: bedbug spread of soil, its natural enemies